Mothers’ Perception of Their Children’s Play in Dhulikhel Hospital, Nepal - Karki, S.; Shrestha, S.; Shrestha, K. (Kathmandu University Medical Journal, 2021)
Background Play is a cherished part of childhood that offers children holistic developmental benefits and parents the opportunity to fully engage with their children. However, modern-day children are spending significantly less time in outdoor play due to a number of factors including technological advancements, more time involved in structured activities, and a greater emphasis on early cognitive learning. Objective To assess perception of mothers on their children’s play. Method This was a descriptive cross-sectional study was carried out among the 228 mothers having at least one child children who attended in Paediatric OPD of Dhulikhel hospital of Nepal from 21st June, 2018 to 16th July, 2019. Ethical approval was obtained from the Institutional Review Committee (IRC) of Kathmandu University School of Medical Sciences (KUSMS). Research instrument was developed by Barnett and was adopted for this study with permission from the author. Systematic random sampling technique was used to select mothers and face to face interview was carried out to collect information. Result Perception on play of children in the mothers was varied. Most of mothers agreed on different subscales of play with mean range 2.07-3.01 in which they were agreed on freedom play with mean score 3.01±0.40, importance of play with mean score 2.93±0.37 and nearly agreed on maternal rule with mean score 2.89±0.50, play safety with mean score 2.92±0.36, child’s choice with mean score 2.96±0.49 and disagreed on imaginative play with mean score 2.42±0.59 and gender typing with mean score 2.07±0.51. Conclusion Although almost all respondents had positive attitudes towards different component of the play, they disagreed on gender typing and imaginative play which is very important for developing problem solving skill of children based on their gender. So, nursing faculties, pediatricians and nurses can use the findings to develop awareness on importance of gender typing and imaginative play among mothers.